Effect of Nutrition on Biomechanical Properties of Bone in Laying Hens and Broilers - Osman Olgun (Turkish Journal of Agriculture: Food Science and Technology)
Leg problems have caused significant economic losses in poultry sector. Bone quality and strong is related to nutrition. In this review, effects of nutrition on bone strength are given to laying hens and broilers. For this, effects of some minerals and feed additives on bone quality were reviewed. Calcium, phosphorus, boron and some feed additives in feeding of hens and broilers are important to strong bone. In addition, the form of calcium resources must be considered in laying hens.